Between Rus’, Byzantium, and the Nomads Tmutarakan’ in the Narrative of the Rusian “Primary Chronicle” - Siwko, Arkadiusz (Studia Ceranea, 2023)
The article is an attempt to provide a source analysis of the mentions of Tmutarakan’ contained in the Primary Chronicle – the oldest surviving monument of medieval Rusian historiography. In the text, particular emphasis is placed on the narrative strategy of the source and the image of the borderlands of Rus’ contained therein. The author reflects on the place of information about events in the remote “exclave” of the Rurikids domain in the story about the dynasty and the territorial expansion of its state and formulates hypotheses about their origin. In addition, using the List of Rusian further and closer gords as a basis, he raises the question of the functioning of Tmutarakan’ in minds of the authors and recipients of later texts.